Enhancing Local Port Competitiveness: Strategies For Facing Challenges From Public Ports and Special Terminals - April Gunawan Malau; Jan Hotman Malau; Albert Gamot Malau; Rosna Yuherlina Siahaan; Marudut Bernadtua Simanjuntak (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research examines the role of local ports in addressing challenges from public ports and special terminals in their vicinity. It focuses on infrastructure, efficiency, connectivity, and competitiveness, using qualitative analysis and a Likert scale questionnaire. Findings reveal that while local ports excel in certain areas, improvements in infrastructure maintenance, operational efficiency, and transport connectivity are needed. Recommendations include investing in infrastructure, improving efficiency, enhancing marketing strategies, fostering collaborations, prioritising sustainability, and focusing on customer satisfaction. Implementing these recommendations can enhance local ports' competitiveness, strengthen their position in the maritime industry, and contribute to regional economic development.